Impacts and Reflections on the Making Meaning Symposium for Small, Independent Libraries - Leonhardt, Eric T. (Evidence Based Library and Information Practice, 2018)
This paper discusses how a small volunteer library changed after attending a symposium on Indigenous Librarianship and metadata. It provides an introduction to the Aboriginal Teacher Education Program Library, how it was formed, and the decision making process behind it. The paper goes on to summarize key points from speakers at the Making Meaning Symposium, and how they challenge the choices made by volunteers. The results have all been positive, and continue to shape discussions about how to best implement what was learned.When we think we know, we think we own something, and we take away from what it represents. - Ambrose Cardinal, personal communication